TRADISI UPACARA RITUAL SIRAMAN SEDUDO SEBAGAI WUJUD PELESTARIAN NILAI-NILAI SOSIAL - Wikan Sasmita (Universitas Negeri Malang, 2018)
The purpose of writing this article is to describe the implementation of ritual ceremonies and the manifestation of the preservation of social values in the ritual ceremonies of the Sedudo ritual shower. The study uses a qualitative approach. Data collection using interviews and documen- tation. Data analysis is carried out by collecting data, reducing data, presenting data, and drawing conclusions. The procedure for implementing the Sedudo Siraman ritual ceremony is (1) sacred dance, (2) 15 girls salute / pray for supplication, (3) the Regent gives klenting, (4) klenting is brought to the spring / pool under the Sedudo grojogan, ( 5) klenting is left to the junkies, (6) the men fill the klenting with water and are handed over to the princesses, (7) holy water is handed over to the caretaker, (8) caretakers and village elders keep the water in the village tomb, (9 ) remarks and inaugurationbytheRegent,(10)recitingprayers,(11)bathingtogether.Thisformofsocialvalues is originalinthecommunityofNganjukdistrict.Thesocialvalues containedintheimplementationof the Sedudo Siraman ritual ceremony are the value of tolerance, the value of compassion, the value of mutual cooperation, the value of harmony, the value of togetherness, the value of cooperation, and family values.